Visual PROMETHEE: Developments of the PROMETHEE & GAIA multicriteria decision aid methods - Mareschal, B.; De Smet, Y. (2009 IEEE International Conference on Industrial Engineering and Engineering Management, 2009)
PROMETHEE and GAIA are multicriteria decision aid methods belonging to the family of outranking methods. PROMETHEE is prescriptive: it provides the decision-maker with rankings of a set of alternative decisions evaluated on several often conflicting criteria. GAIA is descriptive: it uncovers important features of the decision problem and assists the decision-maker in eliciting preferences and finalizing the decision. After a brief summary of the basis of PROMETHEE and GAIA, we focus on the new development of Visual PROMETHEE. We propose several visual representations to enhance the efficiency of the methods. In particular the PROMETHEE Diamond is used to visualize the PROMETHEE I partial ranking and the GAIA Brain representation can be used to facilitate the assessment of the criteria weights. These developments are illustrated on a numerical example.